Focus on the impact of climate change on wetland ecosystems and carbon dynamics - Meng, Lei; Roulet, Nigel; Zhuang, Qianlai; Christensen, Torben R; Frolking, Steve (Environmental research letters, 2016)
The renewed growth in atmospheric methane (CH4) since 2007 after a decade of stabilization has drawn much attention to its causes and future trends. Wetlands are the single largest source of atmospheric CH4. Understanding wetland ecosystems and carbon dynamics is critical to the estimation of global CH4 and carbon budgets. After approximately 7 years of CH4 related research following the renewed growth in atmospheric CH4, Environmental Research Letters launched a special issue of research letters on wetland ecosystems and carbon dynamics in 2014. This special issue highlights recent developments in terrestrial ecosystem models and field measurements of carbon fluxes across different types of wetland ecosystems. The 14 research letters emphasize the importance of wetland ecosystems in the global CO2 and CH4 budget.